2014
DOI: 10.19030/iber.v13i5.8779
|View full text |Cite
|
Sign up to set email alerts
|

Education And Small Business Growth: A Gender Perspective Of Two Divergent Provinces In South Africa

Abstract: The article attempts to identify whether the level of education and gender has an impact on the business growth of SMMEs in a developing economy. The study furthermore looks at the contribution made by the SMME sector from a spatial perspective. The Western Cape is seen as a more affluent province and a bigger contributor to the countrys GDP as opposed to KwaZulu-Natal, which comprises of the former province of Natal and the Zululand homelands. Entrepreneurship can be considered as one of the means of creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
6
2
Order By: Relevance
“…The study found a very strong positive relationship with financial literacy and small firm financial growth in Bangladesh. A good number of previous studies (Smith, McArdle, and Willis 2010;Lusardi and Mitchell 2011;Ganyaupfu 2013;Peters et al 2014) also revealed the similar associations between financial literacy and financial outcomes of firms in different context. The owner-managers are the important resources for the small firm who make plan, use other resources and take all kinds of decisions including the financial and investment decision as well as carry out the functional activities of their business; all of which ultimately affect their financial growth.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The study found a very strong positive relationship with financial literacy and small firm financial growth in Bangladesh. A good number of previous studies (Smith, McArdle, and Willis 2010;Lusardi and Mitchell 2011;Ganyaupfu 2013;Peters et al 2014) also revealed the similar associations between financial literacy and financial outcomes of firms in different context. The owner-managers are the important resources for the small firm who make plan, use other resources and take all kinds of decisions including the financial and investment decision as well as carry out the functional activities of their business; all of which ultimately affect their financial growth.…”
Section: Discussionmentioning
confidence: 56%
“…However, empirical studies revealed that in most of the countries, the level of financial literacy is very low and only a few people understand the basic financial concepts (Cole, Sampson, and Zia 2009;Lusardi and Tufano 2009). Most of the studies (Watson, Stewart, and BarNir 2003;Barringer, Jones, and Neubaum 2005;Ahamad et al 2012;Peters et al 2014) indicated that the higher level of educational background expedite the growth or performance of the small firms.…”
Section: Financial Literacy Of Owner-manager and Small Firm Financialmentioning
confidence: 99%
“…H However, empirical studies reveal that in most countries, the level of financial literacy is very low and only a few people understand basic financial concepts (Cole et al, 2011;Lusardi & Tufano, 2009). Most studies (Barringer et al, 2005;Peters et al, 2014;Watson et al, 2003) indicate that a higher educational background accelerates the growth or performance of small businesses.…”
Section: Financial Behavior and Proactive Employeesmentioning
confidence: 99%
“…In a survey conducted by Peters, Van Gensen, Isaacs, Botha andNaicker (2014:1129) among SMME owners/managers in the provinces of Western Cape and KwaZulu-Natal in South Africa, the successful performance by women owner/managers could be attributed mainly to respondents having equal access to resources (for example finance), as well as diminished constraints in terms of their competencies and a social tendency to pursue higher education. These findings are aligned with the conviction expressed by Ahl (2006), Ahl and Marlow (2012:556) and Henry, Foss and Ahl (2015:19), based on liberal feminist theory, that there should be no difference in the performance of businesses, irrespective of gender, provided women experience no discrimination in access to resource s (finance and education).…”
Section: Women Business Owners Worldwidementioning
confidence: 99%
“…Researchers have concluded that business ownership by women in South Africa should be promoted by providing support in the form of advice, training, access to finance and networks, gender-balanced mentoring in work matters and balancing emotional and work-life issues (Martin & Barnard, 2013:24, 26;Peters et al 2014Peters et al :1136. The GEM 2012 Women's Report (Global Entrepreneurship Monitor 2012 Women's Report, 2012:4) suggests that support for women business owners (which could take the form of advice and services) should take place using support networks, women mentors and local women as role models.…”
Section: Support Programmes Available To Womenmentioning
confidence: 99%